Behavioral and neural correlates of acute and scheduled hunger in C57BL/6 mice. - Christian M Gallardo; Cynthia T Hsu; Keith M Gunapala; Maksim Parfyonov; Chris H Chang; Ralph E Mistlberger; Andrew D Steele (PLoS ONE, 2014)
In rodents, daily feeding schedules induce food anticipatory activity (FAA) rhythms with formal properties suggesting mediation by food-entrained circadian oscillators (FEOs). The search for the neuronal substrate of FEOs responsible for FAA is an active area of research, but studies spanning several decades have yet to identify unequivocally a brain region required for FAA. Variability of results across studies leads to questions about underlying biology versus methodology. Here we describe in C57BL/6 male mice the effects of varying the 'dose' of caloric restriction (0%, 60%, 80%, 110%) on the expression of FAA as measured by a video-based analysis system, and on the induction of c-Fos in brain regions that have been implicated in FAA. We determined that more severe caloric restriction (60%) leads to a faster onset of FAA with increased magnitude. Using the 60% caloric restriction, we found little evidence for unique signatures of neuronal activation in the brains of mice anticipating a daily mealtime compared to mice that were fasted acutely or fed ad-libitum-even in regions such as the dorsomedial and ventrolateral hypothalamus, nucleus accumbens, and cerebellum that have previously been implicated in FAA. These results underscore the importance of feeding schedule parameters in determining quantitative features of FAA in mice, and demonstrate dissociations between behavioral FAA and neural activity in brain areas thought to harbor FEOs or participate in their entrainment or output.